Parents' and Children's Perceptions and Attitudes Towards Traditional and Novel Plant-Based Meat Alternatives: A Scoping Review - Goh AT; Mo Y; McCormack JC; Oey I; Hort J; Peng M (Oxford University Press on behalf of the International Life Sciences Institute, 2025)
The growing popularity of plant-based meat alternatives (PBMAs) as a sustainable dietary option highlights the need to understand family perceptions to support their integration into daily diets. Early-life food preferences often stem from parents or caregivers. This scoping review synthesized existing findings on parents’ and children’s perceptions of traditional and novel PBMAs and identified motivators and barriers to adopting them in family meals. A comprehensive search across 5 databases (Nutrition and Food Sciences, Web of Science, Global Health, Scopus, PsycINFO) was performed on April 1, 2024, using predefined terms. The review adhered to Joanna Briggs Institute (JBI) methodology and PRISMA-ScR reporting guidelines. The Mixed Methods Appraisal Tool was used to assess study quality. Twenty studies were identified: 5 articles on parents or caregivers, 11 studies on children, and 4 articles on parent–child dyads. Parents were more accepting of traditional PBMAs (eg, lentils, tofu, beans, chickpeas), but expressed concerns over the nutritional adequacy, sodium content, and processing of novel PBMAs. Among parents who were non-regular users, traditional PBMAs were viewed mainly as a textural enhancement rather than a nutrient source. By contrast, children were generally more receptive to novel PBMAs compared with parents, particularly when products resembled meat and were linked to environmental and animal welfare benefits. For both parents and children, taste emerged as the primary driver for repeated consumption. Strategies to increase PBMA uptake in families should be focusing on improving the sensory appeal and nutritional profile of these products, enhancing product transparency around ingredients and processing technologies, and providing tailored nutrition education that aligns with existing knowledge and cooking skills. Family-based interventions that address both parental concerns and children’s motivations may be particularly effective in positioning PBMAs as an accepted component of everyday family meals.
Keywords: consumer behaviour; family food choices; food preferences